THE ROLE OF PRICE, PRODUCT ADVANTAGES AND PLACE OF BUSINESS ON CUSTOMER LOYALTY THROUGH SATISFACTION AS A LOCATION VARIABLE (STUDY AT MR KLIWON ARJASA CHIKEN NOODLE STALL) - Stivani Yanti Atmanegara (SEAN Institute, 2022)
Increased competition between countries, especially food businesses so that business stakeholders are expected to provide a sense of satisfaction to consumers. Then after achieving a sense of satisfaction will have a good effect on the level of consumer loyalty. Therefore, it must be noted that the variables that play a role in increasing consumer satisfaction. This research intends to understand to what extent is the level of customer loyalty. The sample is a buyer of chicken noodles at Pak Kliwon Arjasa's shop. The population that is applied is a total of 78 people. Data collection was carried out by distributing questionnaires to chicken noodle buyers at the Pak Kliwon shop. The data processing uses smart PLS where Y1 is the satisfaction variable as the intervening variable, Y2 is the consumer loyalty variable, X1 is the tariff variable, X2 is the product excellence variable, X3 is the place of business variable. The results of this research found a positive and significant relationship between tariffs, product superiority and place of business on consumer loyalty through satisfaction as an intervening variable.